Pure spinal extradural arteriovenous malformation in the thoracolombar region: a case report - Yakar, Fatih; Eroğlu, Ümit; Doğan, İhsan; Uğur, Hasan Çağlar (The European Research Journal, 2019)
Pure extradural spinal arteriovenous malformations (AVMs) are formed with an epidural artery, a nidus and an arterialized intradural vein in the absence of vertebral cavernous hemangioma and uncommon lesions. The most common extradural tumors are metastasis, lymphomas, benign tumors and malignant bony tumors. Herein, we present a-29-year-old Turkish woman with pure extradural mass that histopathologically diagnosed as AVM. When an extradural spinal compressive mass is detected, neurosurgeons should consider on AVM in differential diagnosis and requirement of selective spinal angiography.